Systematic literature review determinants and contribution of restaurant tax to local own-source revenue in Indonesia - Karyanto, Karyanto; Sofyani, Hafiez (Journal of Accounting and Investment, 2025)
Research aims: This research aims to explore in general the previous research related to contribution of restaurant taxes in Indonesia to Local Own-Source Revenue (LOSR) and analyze studies from several angles.Design/Methodology/Approach: This research uses a Systematic Literature Review which consists of three stages, namely the collection stage by entering the search keywords "Contribution" and "Restaurant Tax" and "Regional Original Income" in Google Scholar and Scopus from 2014 to 2023. Articles included in research is assessed based on its ranking in the SINTA and Scopus indexes. The presentation stage is looking for research background, methods and findings. After applying a series of criteria, 44 articles were obtained.Research findings: This systematic literature review found that research on restaurant taxes in Indonesia has been active since 2014, most of it published in the journal SINTA 4, while publications in Scopus are still limited. The majority of research was conducted on the island of Java and used quantitative methods, but most did not include specific theories in their analysis. In general, restaurant tax in Indonesia has not provided an optimal contribution to LOSR, most researchers say that one of the determinants of restaurant tax contribution is the lack of taxpayer compliance and awarenessNovelty: The novelty of this research is more generally looking at the contribution of restaurant taxes in Indonesia and systematic literature review research published in the indexed journals Sinta and Scopus has never been found and carried out